2007
DOI: 10.1002/glia.20532
|View full text |Cite
|
Sign up to set email alerts
|

Microglial PHOX and Mac‐1 are essential to the enhanced dopaminergic neurodegeneration elicited by A30P and A53T mutant alpha‐synuclein

Abstract: alpha-Synuclein, a gene whose mutations, duplication, and triplication has been linked to autosomal dominant familial Parkinson's disease (fPD), appears to play a central role in the pathogenesis of sporadic PD (sPD) as well. Enhancement of neurodegeneration induced by mutant alpha-synuclein has been attributed to date largely to faster formation of alpha-synuclein aggregates in neurons. Recently, we reported that microglial activation enhances wild type (WT) alpha-synuclein-elicited dopaminergic neurodegenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 63 publications
10
127
1
3
Order By: Relevance
“…Of the pattern recognition receptors implicated in microglial activation, macrophage Ag complex-1 (Mac-1) and CD36 (class B scavenger receptor) have been recently reported to mediate asynuclein-induced microglial activation (20,41). Zhang et al (41) reported that a-synuclein directly binds to Mac-1 receptors, which then activate NADPH oxidase to produce ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Of the pattern recognition receptors implicated in microglial activation, macrophage Ag complex-1 (Mac-1) and CD36 (class B scavenger receptor) have been recently reported to mediate asynuclein-induced microglial activation (20,41). Zhang et al (41) reported that a-synuclein directly binds to Mac-1 receptors, which then activate NADPH oxidase to produce ROS.…”
Section: Discussionmentioning
confidence: 99%
“…LPS induces a rapid activation of microglia and a delayed, progressive and selective destruction of nigral dopaminergic neurons both in vivo and in vitro ( [78,77,79]). Finally, using mice carrying a deletion in the gene coding for NADPH oxidase, one major source of intracellular ROS, or in Mac-1 it has been possible to clearly demonstrate that the production of ROS by LPSactivated microglia is directly toxic to neurons as well as the secretion of proinflammatory molecules, which foster neurodegeneration as well ( [182,190,252,265,264]). …”
Section: Animal Models Of Parkinson's Diseasementioning
confidence: 99%
“…Moreover, following the discovery that Syn aggregates can be released from neurons and transmitted to neighbouring cells (Desplats et al, 2009), a study has recently shown that Syn release by SH-SY5Y neuroglioma cells, especially when treated with MPP + neurotoxin, are able to activate the inflammatory response in a microglial cell line (Alvarez-Erviti et al, 2011). Up to this point, research on Syn-mediated cell response has focused primarily on the effects on neuroinflammation (Benner et al, 2008) or microglial activation (Cookson, 2009;Reynolds et al, 2008a;Thomas et al, 2007;Zhang et al, 2007;Zhang et al, 2005) of Syn in its aggregated form. Interestingly, Reynolds and coworkers (Reynolds et al, 2008b) have found that nitrated, aggregated Syn (N-Syn) has a stronger stimulating effect on microglia than that of nitrated but non-aggregated Syn.…”
Section: Syn-induced Microglial Activationmentioning
confidence: 99%